(x-3)=-3x+33

Simple and best practice solution for (x-3)=-3x+33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-3)=-3x+33 equation:


Simplifying
(x + -3) = -3x + 33

Reorder the terms:
(-3 + x) = -3x + 33

Remove parenthesis around (-3 + x)
-3 + x = -3x + 33

Reorder the terms:
-3 + x = 33 + -3x

Solving
-3 + x = 33 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-3 + x + 3x = 33 + -3x + 3x

Combine like terms: x + 3x = 4x
-3 + 4x = 33 + -3x + 3x

Combine like terms: -3x + 3x = 0
-3 + 4x = 33 + 0
-3 + 4x = 33

Add '3' to each side of the equation.
-3 + 3 + 4x = 33 + 3

Combine like terms: -3 + 3 = 0
0 + 4x = 33 + 3
4x = 33 + 3

Combine like terms: 33 + 3 = 36
4x = 36

Divide each side by '4'.
x = 9

Simplifying
x = 9

See similar equations:

| 15x+9= | | 24=3-7x | | 2b+2=3p-7 | | 3x-2=2x+13 | | -12x+3=-8x-6 | | (k+4)=7 | | -2(3+4m)=-18 | | 22=-6-2r | | 10-7n=-25 | | y=2.22x+4.40 | | 35=-7(3+t) | | (-3xy)(7xy)= | | 14n+q=rt-4n | | -10+9x=125 | | 3x+48=2x+24 | | 40x+9.6x=644.80 | | 0=-(x-3)(x-3)+1 | | 5.50(h)=71.50 | | 5w-4w+2w=9 | | 3x+9-9(x+1)=2x+5 | | -5/12*27/15= | | 12+5x=68 | | 15y+17=13y+14 | | 2x-6=5x+22 | | 40-14x=21x-100 | | 0.10+0.05(52-x)=4.50 | | 7=6m-2m+3 | | 7x(6+8)=7*6+7x | | 16x-6153=1143 | | 4(4x-7)(2x+7)=0 | | 170+106+17x=1600 | | x+-4+2x=1 |

Equations solver categories